Progress in Cosmology: an Environmental and Fundamental Science. (29th January 2015) - Rees, Martin
Abstract : Cosmology is a subject that interacts closely with particle physics. But as well as being a fundamental science, it is also the grandest of the environmental sciences: it is concerned with the complex structures that constitute our present cosmos, and how these gradually emerged during the 13.8 billion years that separates us from the 'big bang'.